Hisab Wujud al-Hilal sebagai Politik Identitas Muhammadiyah dalam Diskursus Hisab Ruyat di Indonesia - Maskufa Maskufa (JURNAL INDO-ISLAMIKA, 2016)
Muhammadiyah has consistently been using the method of hisab wujûd al-hilâl (the calculation resulted in a matter of time and the position of beginning new moon of Qamariyyah) for about four decades from 1970 to the present time. This steadiness implies that this method turns to be an ideological identity of Muhammadiyah in determining the first day of the fasting month of Ramadhan. Here, this Islamic mass organization believes that a political effort with a particular identity will have a huge impact on making the method of hisab wujûd al-hilâl as a reliable reference to decide ru`yah (seeing the new moon when the sun set sat on 29 of the Qamariyah month), and on encouraging majority of Muslim in Indonesia to use it.